2020
DOI: 10.1007/s40037-020-00588-y
|View full text |Cite
|
Sign up to set email alerts
|

Case presentation methods: a randomized controlled trial of the one-minute preceptor versus SNAPPS in a controlled setting

Abstract: Introduction One-minute preceptor (OMP) and SNAPPS (a mnemonic for Summarize history and findings; Narrow the differential; Analyze the differential; Probe the preceptor about uncertainties; Plan management; and Select case-related issues for selfstudy) are educational techniques developed to promote learners' expression of clinical reasoning during the case presentation in the workplace. The aim of this present study was to compare the content of the case presentation between the SNAPPS and the OMP methods. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…With regards to the latter, a number of formal teaching strategies which intended to help learners to work with uncertainty, were described. These studies largely fell into two groups: arts-based teaching which addressed issues of uncertainty and ambiguity (Klugman et al 2011 ; Nguyen et al 2016 ; Bentwich and Gilbey 2017 ; He et al 2019 ), and clinical teaching which used SNAPPS, a clinical reasoning scaffold with a specific focus on identifying uncertainties (Nixon et al 2014 ; Sawanyawisuth et al 2015 ; Wolpaw et al 2009 , 2012 ; Fagundes et al 2020 ). Other studies suggested that learners could develop ways to manage uncertainty through use of the Learning-by-Concordance approach (Fernandez et al 2016 ), simulation (Scott et al 2020 ) and a novel equine-facilitated workshop which introduced horses to medical students as “experiential surrogates for ambiguity” (Liou et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the latter, a number of formal teaching strategies which intended to help learners to work with uncertainty, were described. These studies largely fell into two groups: arts-based teaching which addressed issues of uncertainty and ambiguity (Klugman et al 2011 ; Nguyen et al 2016 ; Bentwich and Gilbey 2017 ; He et al 2019 ), and clinical teaching which used SNAPPS, a clinical reasoning scaffold with a specific focus on identifying uncertainties (Nixon et al 2014 ; Sawanyawisuth et al 2015 ; Wolpaw et al 2009 , 2012 ; Fagundes et al 2020 ). Other studies suggested that learners could develop ways to manage uncertainty through use of the Learning-by-Concordance approach (Fernandez et al 2016 ), simulation (Scott et al 2020 ) and a novel equine-facilitated workshop which introduced horses to medical students as “experiential surrogates for ambiguity” (Liou et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst our review suggests that students meet with uncertainty many times during their training, there were few examples of direct teaching, i.e., through arts-based approaches (Klugman et al 2011 ; Nguyen et al 2016 ; Bentwich and Gilbey 2017 ; He et al 2019 ) or clinical cases (Nixon et al 2014 ; Sawanyawisuth et al 2015 ; Wolpaw et al 2009 , 2012 ; Fernandez et al 2016 ; Fagundes et al 2020 ). When compared to other non-technical domains such as communication and team skills, this apparent scarcity is surprising (Buljac-Samardzic et al 2010 ; Berkhof et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Outro fator que se destaca é o protagonismo dos profissionais residentes, ultrapassando o papel de receptores de informações (Marques et al, 2021). A OMP na preceptoria da residência permitiu o desenvolvimento de raciocínio clínico em pesquisa clínica mediante a postura mais ativa dos profissionais residentes (Gatewood;De Gagne, 2019;Fagundes et al, 2020). Tal percepção da preceptora foi corroborada por relatos dos próprios residentes, que demonstraram maior confiança e empoderamento.…”
Section: Discussionunclassified
“…[11,12,19] Considering different barriers mentioned, appropriate learning methods should be chosen to align with the clinical learning environment. Research has identified three methods with sufficient evidence for teaching in clinical practice: the One Minute Preceptor Model, SNAPPS (a mnemonic for Summarize history and findings; Narrow the differential; Analyze the differential; Probe the preceptor about uncertainties; Plan Management; Select case related issues for self-study), [13] and concept mapping. Among these, the One Minute Preceptor Model and SNAPPS are particularly suitable for the demanding daily routine of clinical practice due to their shorter enrollment requirements.…”
Section: Introductionmentioning
confidence: 99%